Optimizing production line of IBS by using simulation model - Alashwal, Ali Mohammed (2006)
Even though IBS has the ability to offer intensive production elements, the rapid increasing demands of providing a shelter for every citizen is enforced enhancing the productivity and the delivery time of IBS. That may obtained by improving the production line layout of the manufacture plant, enhancing production time, and resources utilization. Recently, simulation has begun to be applied in construction industry sector. In this study, â€œWitness 2001â€ program has been testified to be able to build a simulation model for the production line of pre-cast concrete columns and beams. This simulation model offers the alternatives to modify the production line attributes as the capacity of elements treatment area, number of re-useable moulds and labour, breakdown of activities and so on. In fact, that imitates a real plant production line. The model provides the opportunity to identify the optimum production line of the suggested layout. This research presents the results of two simulation models either for columns and beams. The results involve basically on the selection of the appropriate production layout, the required time to produce the assumed amount of columns and beams. Finally, the effect of machineries breakdown and the required resources has been determined in this research.